The Intersection of demographic factors, parental awareness, and attitudes: implications for children's health risks from secondhand tobacco smoke - Elsaihi, Fatma Masoud; Shohaimi, Shamarina; Nadzir, Ohd Noor Hisham Mohd; Puad, Mohd Hazwan Mohd; Rahman, Abdul Hafiz Ab; Elsaieh, Afaf Masaud (The Advanced Institute of Higher Education of Barreiras (IAESB), 2023)
Objective: This study aims to investigate the association between demographic factors, such as age, ethnicity, income, education, and occupation, with parents' perspectives and awareness of the health risks associated with secondhand smoke (SHS), considering the significance of these factors for effective health education and prevention initiatives. Methods: Data were collected from 378 employees working in four higher education institutions in the Klang Valley region of Malaysia. A standardized questionnaire was administered to collect data on demographic characteristics, knowledge, and attitudes towards SHS. Path analysis was employed to examine the relationships between demographic characteristics and parents' knowledge of and attitudes towards the risks of SHS. Results: The study explored how demographic factors, namely age, education, occupation, income level, and ethnicity, influenced parents' knowledge and attitudes towards the health risks of SHS. The results indicated that none of these demographic characteristics had a significant impact on parents' attitudes and knowledge. However, it was observed that parents' financial status significantly and negatively affected their understanding of the health hazards associated with children's exposure to smoking. Conclusions: Protecting children's health and reducing the prevalence of smoking-related illnesses requires parents to enhance their knowledge and foster negative attitudes towards SHS. Developing targeted interventions that address the specific challenges parents face, particularly in relation to their financial circumstances, is crucial to promote a smoke-free environment for children. Research Implications: The study's findings provide insights into the complex relationship between demographic factors and parents' knowledge and attitudes towards SHS. These insights can inform the design of tailored interventions that consider various demographic characteristics to communicate SHS risks and promote healthier behaviours effectively. Originality/Value: This study contributes to the existing literature by examining the influence of demographic factors on parents' perspectives on SHS health risks. The findings underscore the importance of considering demographic characteristics when designing interventions to address SHS exposure and encourage healthier behaviours among parents and caregivers.